Жінки в громадському житті Волині в 30 - 60-х рр. ХІХ ст. - Карліна, Оксана Миколаївна; Karlina, Oksana M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
На підставі аналізу мемуарних джерел та соціального контексту показано активне втягнення жінок у громадське життя, яке спостерігалося на Волині у 30-60-х роках ХІХ ст. У статті показано, що незважаючи на існуючі політичні, соціальні та моральні обмеження, жінки використовували не лише традиційні для своєї статі форми громадської діяльності, але й вдавалися до дієвих форм боротьби: участі в таємних товариствах і політичних маніфестаціях.The article considers the involvement and participation of women in the public life of the community inspired by the processes of adaptation of nobility to the new range of external relationships in Volyn in 30-60-ies of the 19-th cent. The analysis has been done on the basis of the memoir sources and in the social context of that time. Families of the nobles were not only involved into the modernization processes, but they also were the product of that modernization and contributed greatly to the emergence of a new social identity. Good education and certain freedom of personality in the bringing-up process in family promoted the formation of personal social values in women and gave them the opportunity to demonstrate not only traditional for their sex forms and ways of social activity (charities, caring for the sick and disabled, bringing up and educating children), but also to take part in active struggle, joining secret societies and participating in various manifestations.
Women in public life of Volyn ( 30-60-ies of 19-th cent.)
Keywords: таємне товариство „Союз польського народу”; Єва Фелінська; політичні маніфестації; Січневе повстання 1863 р.; Волинська губернія; Eva Felinska; secret society “Polish People Union”; political manifestations; January Rebellion of 1863; Volynian Gubernia ( province)